2016
DOI: 10.1038/nrn.2016.163
|View full text |Cite
|
Sign up to set email alerts
|

Towards a mechanistic understanding of the human subcortex

Abstract: The human subcortex is a densely populated part of the brain, of which only 7% of the individual structures are depicted in standard MRI atlases. In vivo MRI of the subcortex is challenging owing to its anatomical complexity and its deep location in the brain. The technical advances that are needed to reliably uncover this 'terra incognita' call for an interdisciplinary human neuroanatomical approach. We discuss the emerging methods that could be used in such an approach and the incorporation of the data that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
97
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 138 publications
1
97
0
Order By: Relevance
“…The field's preponderance for the cerebral cortex, coupled with technical challenges inherent to subcortical imaging [32][33][34] , has led to the subcortex remaining a terra incognita 35 . Through the provision of high-quality, ultra-high field strength MRI data, collaborative initiatives such as the HCP 18 herald new opportunities to overcome some of the challenges associated with reliably imaging this deep and anatomically complex brain structure.…”
Section: Discussionmentioning
confidence: 99%
“…The field's preponderance for the cerebral cortex, coupled with technical challenges inherent to subcortical imaging [32][33][34] , has led to the subcortex remaining a terra incognita 35 . Through the provision of high-quality, ultra-high field strength MRI data, collaborative initiatives such as the HCP 18 herald new opportunities to overcome some of the challenges associated with reliably imaging this deep and anatomically complex brain structure.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of empirical evidence suggests that to-date we are only starting to understand the function of these nuclei and their subdivisions for human behavior and cognition in health (1) and disease (2)(3)(4)(5). One reason for this lack of understanding is due to severe technical difficulties in assessing these nuclei in-vivo in humans using non-invasive conventional magnetic resonance imaging (MRI) (6). Here, we show that the visual lateral geniculate nucleus (LGN) and its cytoarchitectonic subdivisions can be identified in humans both in-vivo and postmortem using advanced microstructure-informed quantitative MRI strategies.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of the LGN's main neuronal layers (often coined as M and P subdivisions) in humans in-vivo faces considerable challenges. First, the LGN's small size, ranging from only 91-157 mm 3 in humans (12), and deep location within the brain makes it difficult to map the LGN using non-invasive MR imaging techniques (6). Second, conventional image resolutions in invivo MR examinations (structural MRI ~1mm, functional MRI ~2.5mm isotropic resolution) are likely insufficient to fully disentangle distinct signal contributions of M and P subdivisions due to partial volume effects (13).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that using binarized VTAs (that would model all-or-nothing activations) could predict slightly less variance in clinical outcomes in comparison to using CONNECTIVITY LINKS STN-DBS WITH DEPRESSIVE SYMPTOMS 6 weighted VTAs such as the E-field gradient vector magnitudes 20 . Binary VTAs are based on specific thresholds that assume a certain type of axon diameter and orientation and do not grasp the anatomical complexity of the subcortex 25 . To account for this general limitation of the VTA concept, we repeated all analyses using the unthresholded E-field magnitude instead of the VTAs 26 .…”
Section: Localization Of Dbs Electrodesmentioning
confidence: 99%